2002
DOI: 10.1210/jcem.87.3.8313
|View full text |Cite
|
Sign up to set email alerts
|

Serum Leptin Level Is a Predictor of Bone Mineral Density in Postmenopausal Women

Abstract: To assess whether leptin is an independent predictor of bone mineral density (BMD) in postmenopausal women, we studied the relationships of BMD to serum leptin, 25(OH)D, 1,25(OH)(2)D, PTH, E2, dehydroepiandrosterone sulfate, GH, IGF-I, creatinine clearance, calcium intake, fat mass, and lean mass in 107 women aged 50-90 yr. We also related serum leptin to markers of bone formation [serum bone alkaline phosphatase and osteocalcin (OC)] and resorption (urine C-telopeptide of type I collagen). In stepwise multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(43 citation statements)
references
References 69 publications
5
33
0
5
Order By: Relevance
“…Percentage body fat was also 14·9 (SD 2·0) % greater in the HFS v. LFCC cohort (P, 0·001). As bone mineral density and bone size are influenced by total body mass (30) , and as bone mineral density influences bone strength (31) , structural properties presented below were adjusted (divided by grams of body mass) as has been done previously in studies where body weight differs substantially between groups (15,24,25,32 -35) .…”
Section: Body Massmentioning
confidence: 99%
“…Percentage body fat was also 14·9 (SD 2·0) % greater in the HFS v. LFCC cohort (P, 0·001). As bone mineral density and bone size are influenced by total body mass (30) , and as bone mineral density influences bone strength (31) , structural properties presented below were adjusted (divided by grams of body mass) as has been done previously in studies where body weight differs substantially between groups (15,24,25,32 -35) .…”
Section: Body Massmentioning
confidence: 99%
“…On the other hand, Madsen et al (19) suggest that the body weight composition, including the lean and fat masses, might be more important than the body weight individually, suggesting that the fat, as a substrate to the conversion of the androgen to estrogen (26) may be related to the BMD both due to hormonal factors because of their importance in regulating sexual hormones in the BMD (5,24) , and to mechanical factors. Related to the lean mass, it can be related to the BMD because although they are structurally independent, both respond to the same atrophy and hypertrophy stimuli (25) .…”
Section: Bmd Muscular Strength and Body Compositionmentioning
confidence: 99%
“…Although the majority of studies emphasize the effect of the type of the physical exercise on the BMD, other factors seem to interfere in that variable as well, such as the muscular strength (25) and the body composition (6,19,26) . In this perspective, regardless the level of the physical activity, some studies have shown that BMD in physically active output athletes or even the sedentary ones seem to pursue an association to their muscular strength developed according to the type of the physical exercise or daily activity, and their body composition (6,19,25,26) . Based on the aspects approached in the above mentioned studies, the aim of this article is to make a review on the effects of different sportive modalities and the strength training on the bone health, and also to analyze its possible benefic or harmful mechanism.…”
mentioning
confidence: 99%
“…There are studies where a positive association has been found between leptin and BMD (14,23) while there are also studies reporting no significant association (8,24) or a negative association (13,25) Yamauchi et al (26) claimed that there is a relation between low plasma leptin levels and vertebral fractures in postmenapousal women and thus circulating leptin might play a physiological role in improving bone mass quality. Unsurprisingly, insulin values of the patients were significantly higher than controls, independent of gender.…”
Section: Discussionmentioning
confidence: 99%